Optimization of tourism evaluation through a website analytics dashboard at Travelogin Tour and Travel - Nilam Chanthika; Esya Alhadi; Hadi Jauhari (International Journal of Applied Sciences in Tourism and Events, 2025)
This study aims to optimize the tourism evaluation process through the design and implementation of a website-based analytic dashboard at Travelogin Tour and Travel. The research was motivated by the inefficiency of conventional methods such as Google Forms, which often result in low response rates and slow data processing. Data was collected through user feedback submitted directly on the newly developed dashboard interface, replacing the previous manual collection via Google Forms. The system was developed using the Waterfall model, consisting of stages including requirement analysis, system design, implementation, and testing. The dashboard was built using Laravel, Bootstrap, and MySQL, and features Net Promoter Score (NPS) visualizations, participant statistics, and automated summaries of feedback. The main results show that the dashboard significantly streamlines the evaluation process, facilitates faster complaint resolution, and enables more effective data-driven decision making. These improvements contribute to better tracking of customer satisfaction, enhanced service quality, and increased competitiveness for Travelogin in the tourism sector. This research demonstrates that integrating website-based analytic tools in tourism operations can support more efficient evaluation mechanisms and improve organizational performance.